Design and construction of a device for facilitating the learning of Braille literacy system (2016)
(Eng) This paper describes the design and implementation of a mechatronic device to facilitate learning of Braille literacy system, aimed primarily at children between 4 and 8 years, taking into account physical and functional aspects that guarantee comfort, motivation, permanence and accessibility Braille language. The device communicates wirelessly with a computer and it is integrated with software that serves as a tutor, telling the user that the character is being studied by an audible signal, evaluating what he writes emitting a sound of right or wrong and showing on the monitor for support staff / teacher supervises learning. The functionality of the equipment was validated visually impaired children.